DEVELOPMENT OF ACADEMIC ADMINISTRATION AND STUDENT SERVICES SYSTEM AT THE FACULTY OF ENGINEERING AND MARITIME TECHNOLOGY, RAJA ALI HAJI MARITIME UNIVERSITY - Berta Erwin SLAM; Rifaldi Herikson; Sepli Yandri (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
The Administrative Information System is a system developed to enhance the efficiency of administrative management, involving student graduation reporting and visit letter processing. The development of the information system utilizes the Waterfall method through stages of planning, requirements analysis, design, development, and testing. The development process begins with identifying administrative issues, followed by collecting user requirements data through interviews and observations. The results of this stage are then translated into a system design that includes system architecture, interface design, and database structure. This system is expected to provide benefits, particularly in accelerating administrative processes, facilitating archiving, improving data accuracy, and delivering information more quickly and in a structured manner. The designed system not only supports the operational activities of the faculty in managing administration but is also expected to serve as a reference for the development of similar systems in other educational institutions.